Applied English phonology - Yavas, Mehmet S.; Wiley InterScience (Online service) (Oxford ; Malden, MA : Wiley-Blackwell, 2011)
"Applied English Phonology has been extensively revised and expanded, using an accessible style and numerous exercises to explore the fundamental aspects of the English sound system. Covers the fundamental aspects of the English sound system, including basic phonetic elements; phonemics; allophonic rules of English consonants and vowels; phonotactics; and stress and intonation Includes brand new sections on U.S. regional vowel shifts, sociophonetic variations, and the role of perception and Optimality Theory with reference to second language phonology Accompanied by new sound files for numerous transcription exercises Incorporates extensive exercises to aid students in understanding and assimilating the material more effectively Supported by an Instructors' Manual for lecturers, available on publication at www.wiley.com/go/yavas"--
"Applied English Phonology responds to the need for a practical and accessible source on applied phonology for students from applied linguistics, TESOL, and speech pathology programs. It does so by covering the fundamental aspects of the English sound system, including basic phonetic elements, phonemics, allophonic rules of English consonants and vowels, phonotactics, and stress and intonation. This new edition has been thoroughly revised and extended and is now accompanied by numerous sound files for transcription practice, new exercises, explanations of sociophonetic variation, and systematic and expanded coverage of regional vowel shifts in the United States. It also includes entirely new sections on the role of Optimality Theory and perception in second language phonology. All chapters include extensive and updated exercises to aid students in both their grasp of the subject and their effective assimilation of material"--
Front Matter -- Phonetics -- Phonology -- English Consonants -- English Vowels -- Acoustics of Vowels and Consonants -- Syllables -- Stress and Intonation -- Structural Factors in Second Language Phonology -- Spelling and Pronunciation -- Recommended Readings -- Appendix: List of Sound Files -- Glossary -- References -- Index -- to the Exercises of Applied English Phonology.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: English language -- Study and teaching -- Foreign speakers; English language -- Phonology; English language -- Phonology; English language -- Study and teaching -- Foreign speakers; Electronic books